2017
DOI: 10.1021/acsnano.7b01714
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Cross-Aligned Silver Nanowire Electrodes for Flexible, Transparent, and Force-Sensitive Mechanochromic Touch Screens

Abstract: Silver nanowire (AgNW) networks are considered to be promising structures for use as flexible transparent electrodes for various optoelectronic devices. One important application of AgNW transparent electrodes is the flexible touch screens. However, the performances of flexible touch screens are still limited by the large surface roughness and low electrical to optical conductivity ratio of random network AgNW electrodes. In addition, although the perception of writing force on the touch screen enables a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
276
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(279 citation statements)
references
References 74 publications
2
276
0
1
Order By: Relevance
“…For 8 nm silica sol nanoparticles, when the concentration of silica sol increases to 80 ppm, the AgNWs ink contains a huge number of nanoparticles with diameter of 8 nm, which fully decorate the surface of the AgNWs, affording AgNWs with larger diameter. According to previous research, [49][50][51] the transmittance of TCEs is related to the area coverage A c as shown in eqn (1) and (2). Therefore, with increasing diameter of AgNWs, the A c increases, and the transmittance decreases.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…For 8 nm silica sol nanoparticles, when the concentration of silica sol increases to 80 ppm, the AgNWs ink contains a huge number of nanoparticles with diameter of 8 nm, which fully decorate the surface of the AgNWs, affording AgNWs with larger diameter. According to previous research, [49][50][51] the transmittance of TCEs is related to the area coverage A c as shown in eqn (1) and (2). Therefore, with increasing diameter of AgNWs, the A c increases, and the transmittance decreases.…”
mentioning
confidence: 84%
“…At present, AgNWs can be easily synthesized using the well-established polyol reduction method in the presence of polyvinylpyrrolidone (PVP), [23][24][25] but the residual PVP ligands will form an insulating layer around the AgNWs, resulting in high contact resistance at NW-NW junctions. A number of strategies have been developed to improve the conductivity of AgNWs thin lms, including mechanical pressing, 26,27 plasmonic welding, 10,28 thermal annealing, 27,29,30 adding soldering agents, [31][32][33] capillary-force-induced cold welding, 34 nanowire assembly, 2,35 and photochemical welding. 36,37 However, these strategies either need harsh conditions or are not efficient enough for large area fabrication.…”
Section: -16mentioning
confidence: 99%
“…[95,96] However,i ts stiff and brittle properties limit its further progressi nf lexible touch devices because the future touch panelss hould be stretchable or at least flexible in order to interact with human body.T herefore,s ome candidates, such as metal nanostructures, graphene, CNTs, and conductingp olymers, are investigating to displace indium tin oxide for their combinationo fh igh conductivity and stretchability. [97][98][99][100][101][102][103][104] For example, ah ighly flexible and transparent conductor was fabricated by using Ag nanowirea nd conducting polymer. [105] The neighboring Ag nanowires weren anosoldered by PEDOT:PSS coating at the nanowire junctions, whichr educed contacting resistance of the hybrid composite film.…”
Section: Touch Panelsmentioning
confidence: 99%
“…Therefore, the Ag NWs are believed to be one of the most promising electrode materials for the flexible photovoltaic or optoelectronic devices. [39][40][41][42] The performance of the metal NW-based electrode generally increases with the decrease in the diameter of the NW, while the increase in the NW length/diameter aspect ratio will reduce light scattering and decrease the resistance in the film. [43][44][45][46][47][48][49] Therefore, in this study, Ag NWs with an average aspect ratio of 5000 (average diameter of B30 nm and length of 100-200 um, Fig.…”
Section: Solution-processed Flexible Electrodementioning
confidence: 99%